The Implementation of Interactive Multimedia for the First-grade Beginning Readers of Elementary School - Dika Wulandari; Siti Rochmiyati; Erna Nuryani; Banun Havifah Cahyo Khosiyono; Ganis Nurma Febriarti; Maisaroh Farida Nurrohmah; Mimin Nurnaini Zumaroh (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to improve students reading skills using interactive multimedia for the first grade of elementary school. This study is used classroom action research (CAR) by Kemmis & Taggart model design. The research participants were 18 first-grade students of elementary school. Data collection was used observation and performance assessments in the form of preliminary reading practice. The findings demonstrated that interactive media might help first-grade elementary school enhance their early reading abilities. The average value before being given action of 59.7%, which is an increase in early reading skills, can be noted. The average value before being given action was 59.7%, which is in the sufficient group; then climbed in the first cycle to 73.6 percent, which is in the good category; then increased again in the second cycle to 93.1 percent, which is in the very excellent category. As a result, this study may be considered a success because the success markers established in cycle II were satisfied.